2001
DOI: 10.1530/eje.0.1450477
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-kinase inhibits megalin-mediated transcytosis of thyroglobulin across thyroid epithelial cells at a post-sorting level

Abstract: Background: Phosphoinositide 3-kinase (PI3-K) is implicated in various cellular processes involving signaling, including intracellular traf®cking. PI3-K has been shown to play a part in both receptorand non-receptor-mediated transcytosis across cultured kidney cells and undifferentiated thyroid cells. Objective: To investigate the role of PI3-K in transcytosis of thyroglobulin (Tg) across differentiated cultured Fisher rat thyroid cells (FRTL-5 cells) ± a process known to be mediated by megalin, a member of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In L2 cells, which express high levels of megalin, β2gpI binds to megalin and RAP is known to inhibit its uptake ( 16 ). Insulin internalization is also mediated by megalin, but RAP has no effect on insulin uptake in L2 cells ( 13 ). To study the effect of RAP on insulin and β2gpI endocytosis in WKPT cells, we monitored the uptake of Cy2-insulin or Cy2-β2gpI in the presence of various concentrations of RAP ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In L2 cells, which express high levels of megalin, β2gpI binds to megalin and RAP is known to inhibit its uptake ( 16 ). Insulin internalization is also mediated by megalin, but RAP has no effect on insulin uptake in L2 cells ( 13 ). To study the effect of RAP on insulin and β2gpI endocytosis in WKPT cells, we monitored the uptake of Cy2-insulin or Cy2-β2gpI in the presence of various concentrations of RAP ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Retinol binding protein (RBP) uptake in vivo is also mediated almost entirely by megalin, as suggested by the absence of RBP-containing granules in the PT of megalin knockout mice ( 7 ). In immortalized rat renal proximal tubule (IRPT) cells, RBP transcytosis is also mediated by megalin, but RBP transport to the lysosome and subsequent degradation (55% of internalized RBP) are independent of megalin ( 13 ). Therefore, in the IRPT model, other megalin-independent mechanisms of endocytosis must account for RBP degradation: other non-megalin receptors, or fluid-phase pinocytosis, has been suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in thyroid cells TSH activates this pathway by elevating the level of cAmP in the cells through the activation of adenylyl cyclase, a downstream effecter of the TSh receptor [28,29]. marino et al [30] also demonstrated that PI3k exerted an inhibitory effect on megalin-mediated Tg transcytosis across the cultured FRTL-5 cells. It has been postulated that Tg transcytosis plays an important role in the regulation of thyroid function [31].…”
Section: Discussionmentioning
confidence: 99%
“…Megalin and cubilin transport vitamin D, complexed to its serum binding protein. Receptor endocytosis can generate rapid intracellular signals via the Rab5/PI3-kinase pathway [91]. However and from knockout studies, we have excluded the involvement of megalin and cubilin as to the differentiating potency and selectivity of our analogues of 1,25D3 [92].…”
Section: Unfinished Business Regarding the Action Of 125d3 On Haematmentioning
confidence: 99%